COMPARATIVE ANALYSIS OF THE FILTRATION POTENTIAL OF LIGHT GREYWATER THROUGH VARIOUS MEDIA - Singh, Vandana; Kaur, Amarjeet; Gupta, N. C. (Malaysian Journal of Science, 2020)
Water scarcity is an emerging problem across the globe and therefore planners have started promoting the concept of reuse in sustainable planning for conserving water resources. The centralized reuse of treated wastewater is an expensive option and hence decentralized reuse of treated greywater (light and dark) needs to be popularized through simple inexpensive methods like filtration and adsorption. Greywater recycling extends a sustainable pathway in which freshwater resource is conserved and wastewater generation is minimized. Moreover, light greywater can be successfully treated through low-tech filters owing to its weaker strength. In this study, the potential of using low cost waste material as filtering media for treating light greywater was analyzed and possibility of providing prior preliminary treatment to light greywater entering media was assessed using geotextile. The experimental results showed that geotextile used in the study was efficient enough in removing considerable amount of TSS. The study investigates that the low cost media like Rice - husk, Rice husk ash, Sugarcane bagasse, Sugarcane bagasse ash used in treating light greywater could remove BOD, COD, TSS, NO3 and PO4 partially while crushed glass could only remove considerable amount of BOD, COD and TSS.